Nanovesicle Formulation Enhances Anti-inflammatory Property and Safe Use of Piroxicam - Mbah, Chukwuemeka; Ogbonna, Josephat; Nzekwe, Ifeanyi; Ugwu, George; Ezeh, Richard; Builders, Philip; Attama, Anthony; Adikwu, Michael; Ofoefule, Sabinus (Pharmaceutical Nanotechnology, 2021)
Background: Enhanced utilization of certain drugs may be possible through the development of alternative delivery forms. It has been observed that NSAIDs have adverse gastrointestinal tract effects such as irritation and ulceration during anti-inflammatory therapy. This challenge may be overcome through nano topical formulations. Objective: This study aimed to explore the potentials of a transdermal nanovesicular formulation for safe and enhanced delivery of piroxicam (PRX), a poorly water-soluble NSAID. Methods: Preformulation studies were conducted using DSC and FTIR. Ethosomal nanovesicular carrier (ENVC) was prepared by thin-film deposition technique using Phospholipon® 90 H (P90H) and ethanol and then converted into gel form. The formulation was characterized using a commercial PRX gel as control. Permeation studies were conducted using rat skin and Franz diffusion cell. Samples were assayed spectrophotometrically, and the obtained data was analyzed by ANOVA using GraphPad Prism software. Results: The preformulation studies showed compatibility between PRX and P90H. Spherical vesicles of mean size 343.1 ± 5.9 nm, and polydispersity index 0.510 were produced, which remained stable for over 2 years. The optimized formulation (PE30) exhibited pseudoplastic flow, indicating good consistency. The rate of permeation increased with time in the following order: PE30 > Commercial, with significant difference (p< 0.05). It also showed higher inhibition of inflammation (71.92 ± 9.67%) than the reference (64.12 ± 7.92%). Conclusion: ENVC gel of PRX was formulated. It showed potentials for enhanced transdermal delivery and anti-inflammatory activity relative to the reference. This may be further developed as a safe alternative to the oral form.
Keywords: anti-inflammation